Evaluating Disparities in COVID‐19 Clinical Outcomes Among Patients With Cirrhosis in North America and Europe—An International Registry Study - Umar Hayat; Andrew M. Moon; Manesh K. Gangwani; Fariha Hasan; Thomas Marjot; A. Sidney Barritt IV; Wasique Mirza; Duane Deivert; Muhammad Aziz; Dushyant Singh Dahiya; Hassam Ali; Sumant Inamdar; et al. (JGH Open)
ABSTRACT Background Patients with decompensated cirrhosis have a higher risk of hospitalization, ICU admission, and death from COVID‐19. The impact of demographics on these outcomes remains uncertain. Methods The SECURE‐Liver and COVID‐Hep databases were utilized to evaluate disparities in COVID‐19 outcomes. Patients were stratified by North American and European cohorts. Bivariate and multivariable logistic regression was performed. Results A total of 718 cirrhosis patients with COVID‐19 were evaluated. In the North American cohort, Black patients had more comorbidities (CI: 1.86 vs. 1.83, p < 0.01), higher rates of hospitalization (77% vs. 85%, p < 0.01), ICU admission (27% vs. 40%, p = 0.05), and death (18% vs. 28%, p = 0.07). Hispanic patients had the lowest adverse outcome rates. In the European cohort, White patients had more comorbidities (CI; 1.63 vs. 1.31, p = 0.02), but non‐White patients had higher hospitalization rates (82% vs. 67%, p = 0.01), ICU admissions (15% vs. 18%, p = 0.04), and lower mortality rates (28% vs. 34%, p = 0.01). Conclusion Black patients in North America had higher hospitalization, ICU admission, and death rates. In the European subgroup, White patients had higher death rates than non‐White patients. These disparities became statistically insignificant after adjusting for confounders, suggesting that non‐liver‐related comorbidities might increase the risk of adverse outcomes.